Mythical places - Oliveira, Livia de [UNESP] (Univ Federal Fluminense, 2015)
The mythical places remain present in the imagination and the reality of human life. They are still very much ingrained in the cultures and symbols, both past and present. In human culture, myth is not simply a system of dogmatic beliefs, it is also based on actions, historical images or geographical representations. Moreover, the mythical spaces responds to feelings and needs that bring us a magical and mysterious world, full of benefical or harmful beings.
Keywords: Myths; Places; Spaces; People; Things